2006
DOI: 10.1111/j.1467-8306.2006.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Animated Maps with Static Small-Multiple Maps for Visually Identifying Space-Time Clusters

Abstract: Although animated maps are widely promoted as ideal vehicles for learning and scientific discovery, there has been little empirical work that demonstrates their relative effectiveness in relation to static small-multiple alternatives. In this article, we attempt to clarify the issues related to the potential of animation from an explicitly geographic perspective, but one that is also grounded in broader cognitive science and human-computer interaction considerations. We compared the effectiveness of animated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 27 publications
5
86
2
3
Order By: Relevance
“…Sin embargo, estas técnicas no se popularizaron hasta que software y hardware económicos y baratos estuvieron disponibles en los años noventa; en tanto que casi no se realizaron ejemplos de animaciones cartográficas durante los años setenta y ochenta. Al mismo tiempo aumentó el conocimiento empírico sobre las opciones para conseguir un mejor entendimiento de los fenómenos a partir de visualizaciones dinámicas: Por ejemplo observaron Griffin et al (2006) en una investigación empírica que los participantes en el estudio lograron identificar clusters más rápida y precisamente en representaciones dinámicas que en representaciones estáticas, mientras, Dorling y Openshaw (1992), usando animaciones, encontraron concentraciones (tanto en el espacio como en el tiempo) de casos de leucemia en el norte de Inglaterra, que habían sido desconocidas anteriormente. Por lo tanto se intentará en los siguientes capítulos, en primer lugar, exponer las características particulares de datos temporales, para poder mostrar, en segundo lugar, cómo estas particularidades pueden ser implementadas tanto dentro de los Sistemas de información Geográfica (SIG) como afuera de los mismos.…”
Section: Introductionunclassified
“…Sin embargo, estas técnicas no se popularizaron hasta que software y hardware económicos y baratos estuvieron disponibles en los años noventa; en tanto que casi no se realizaron ejemplos de animaciones cartográficas durante los años setenta y ochenta. Al mismo tiempo aumentó el conocimiento empírico sobre las opciones para conseguir un mejor entendimiento de los fenómenos a partir de visualizaciones dinámicas: Por ejemplo observaron Griffin et al (2006) en una investigación empírica que los participantes en el estudio lograron identificar clusters más rápida y precisamente en representaciones dinámicas que en representaciones estáticas, mientras, Dorling y Openshaw (1992), usando animaciones, encontraron concentraciones (tanto en el espacio como en el tiempo) de casos de leucemia en el norte de Inglaterra, que habían sido desconocidas anteriormente. Por lo tanto se intentará en los siguientes capítulos, en primer lugar, exponer las características particulares de datos temporales, para poder mostrar, en segundo lugar, cómo estas particularidades pueden ser implementadas tanto dentro de los Sistemas de información Geográfica (SIG) como afuera de los mismos.…”
Section: Introductionunclassified
“…In studies reviewed by Tversky and colleagues, typical 'success' measures are either response time, also known as completion time (a measure of efficiency) or accuracy of response (a measure of quality). In some experiments comparing map animations with static small multiple displays participants answer more quickly, but not more accurately, with animations (Koussoulakou and Kraak, 1992); in other experiments they take longer, and answer fewer questions more accurately (Cutler, 1998), or the time it takes to answer the question does not matter for accuracy at all (Griffin et al, 2006).…”
Section: Cognitively Adequate Animation Designmentioning
confidence: 99%
“…light type, position, distance, angles, colour attributes). The speed with which an animation is viewed is crucial (Griffin et al, 2006) and whether the viewing order of the frames in an animation is predefined (i.e. without any interaction mechanisms) (Hegarty, Kriz and Cate, 2003).…”
Section: Cognitively Adequate Animation Designmentioning
confidence: 99%
“…We set our duration time as 1, 2, and 3 sec for the experiment. We referred to Griffin et al (2006) s duration time, which was 5, 7, 9, and 11 sec for 6 scenes.…”
Section: Scene Durationmentioning
confidence: 99%
“…In response to this necessity, recent research projects on animated maps have conducted various experiments using survey-based experiments and eye tracking experiments, with the adoption of methods and theories from psychology and vision studies (Montello, 2002;Andrienko et al, 2010). These empirical studies have addressed a wide range of research topics, including comparisons of static small-multiple maps and animated maps (Kossoulakou and Kraak, 1992;Slocum et al, 2004;Griffin et al, 2006), comparisons between visual variables effectiveness in animated maps or interactive maps (Cinnamon, 2009;Çöltekin et al, 2009;Garlandini and Fabrikant, 2009;Hegarty et al, 2010), and the impact of interactivity (Mayer, 2001;Mayer and Chandler, 2001) and dynamic variables such as rate of change and abrupt or smooth transitions (Goldsberry and Battersby, 2009;Fish, 2010). Some studies have concluded that dynamic animated maps that are too complex leads to difficulties in conveying information (Bétrancourt and Tversky, 2000;Morrison and Tversky, 2001;Goldsberry and Battersby, 2009), because of human cognitive limits such as split attention, retroactive inhibition, and cognitive overload (Harrower, 2007).…”
Section: Introductionmentioning
confidence: 99%